Establishing a consensus on wound infection definitions. (1st December 2022) - Haesler, Emily; Swanson, Terry; Ousey, Karen; Larsen, Donna; Carville, Keryln; Bjarnsholt, Thomas; Haesler, Paul
Abstract : Objectives: The aim of this study was to establish an international, interorganisational consensus on wound infection terminology. Methods: This project consisted of definition scoping and a Delphi process to produce a consensus glossary for 18 wound infection terms. Recent guidelines/consensus documents were reviewed to identify 2–4 definitions for each term. An online consensus process was undertaken using the RAND Appropriateness Method, a consensus method for panels to reach agreement. International wound organisations nominated experts to participate, from whom 21 participants were selected to represent different organisations, geographic regions and disciplines. In the first consensus round, each term was presented alongside 2–3 definitions and participants nominated their preferred definition, with the majority vote used to select a baseline definition. The consensus process then proceeded, with participants using a 9-point Likert scale to score their level of agreement or disagreement with the definition for each term. Participants also provided a justification outlining the reason behind their rating. At the end of each round, an index was calculated to provide a quantitative evaluation indicating whether agreement or disagreement had been reached. Results: Reasoning statements were summarised and the definitions were adjusted to incorporate concepts identified by participants. The adjusted definition was presented in the next consensus round, together with the reasoning statements. Terms for which a final definition was not achieved in three consensus rounds were finalised with preferential voting using 2–3 definitions that had reached consensus. Project progress and significance: The project generated a glossary of wound infection terms, endorsed through participation of 15 international organisations, for dissemination of guidelines and clinical decision-making/teaching tools.